Cathepsin D is released after severe tissue trauma in vivo and is capable of generating C5a in vitro - Huber-Lang, Markus; Denk, Stephanie; Fulda, Simone; Erler, Ellen; Kalbitz, Miriam; Weckbach, Sebastian; Schneider, E. Marion; Weiss, Manfred; Kanse, Sandip M.; Perl, Mario (Molecular Immunology, 2012)
In response to severe tissue trauma several danger sensing and signalling cascades are activated, including the complement and the apoptosis systems. In polytrauma patients, both the early activation of the complement cascade with an excessive generation of the potent anaphylatoxin C5a and the induction of apoptosis have been shown to modulate the post-traumatic immune response. However, little is known about a direct interaction between the complement and apoptosis systems after severe tissue trauma. Therefore the focus of the present study was to elucidate the interplay between the central complement component C5 and the pro-apoptotic aspartic protease cathepsin D.In vivo, the cathepsin D plasma concentration of multiple injured patients was markedly increased when compared to healthy volunteers. In vitro incubation of C5 with cathepsin D resulted in a concentration- and time-dependent generation of C5a, which was inhibited by the aspartate protease inhibitor pepstatin A. Immunoblotting and sequencing analysis indicated that the C5 cleavage product represents the native form of human C5a, also exhibiting chemotactic activity for human neutrophils.In conclusion, these data show for the first time that cathepsin D is increased in plasma early after severe tissue injury. Furthermore, the results provide in vitro evidence of cleavage of C5 by an aspartic protease with subsequent generation of functional C5a, which represents a new path of complement activation. © 2012 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Apoptosis; C5a; Cathepsin d; Complement; Polytrauma